Supremasi Pemerintahan di bawah Agamawan: Menilik Strategi Diskursif Ruhulloh M. Khomeini dalam Revolusi Islam Iran - Khusaila, Rika Leli Dewi (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: Ruhollah Musavi Khomeini was a multifaceted revolutionary figure. His engagement with various scholarly discourses, prophetic historicity, and the political realities of his era profoundly influenced him. The synthesis of these influences eventually formed the new Khomeini, characterized by a pragmatic socio-political outlook. This outlook was manifested in his mission to oppose the secular regime of Reza Shah and establish an Islamic government. Based on this phenomenon, this research aims to discuss academic questions regarding Khomeini’s strategy in founding an Islamic government. It concludes that Khomeini’s political involvement in Iran was closely linked to the political realities he faced and the horizontality of Shia theology. His primary strategy was non-military, involving the integration and reinterpretation of various ideas, including monotheism, Shia theological doctrines, ‘irfani (mystical knowledge), Islamic law, and the texts of the Qur’an and the Prophet’s hadiths. This religio-political strategy effectively toppled the Pahlavi regime, leading to the establishment of an Islamic government